The Effect of Carbohydrate Addition in Aquaculture Media towards Production of Intensive Tilapia Culture (Oreochromis niloticus) - Purnomo, Panca Dias (Journal of Aquaculture Management and Technology, 2012)
Biofloc technology was able to overcome the problem of aquaculture waste and increase aquaculture productivity. This study was aimed to determine the effect of additional carbohydrate in culture media towards productivity of cultured tilapia (O. niloticus). The treatments were addition of tapioca (A), molasses (B), and without the addition of carbohydrate (C). Stocking density used in this experiment was 50 tilapia/m2 with initial weight 15:17±0.32g. Fed was applied at 3% of weekly total fish biomass per day. Tilapia was cultured for 35 days with minimum water exchange. The results showed that the addition of carbohydrates into the culture media effected significantly (P <0.05) towarded net production, growth and food conversion ratio (FCR). There was no difference in fish survival rate among the treatments. Production achieved in the treatments A, B, and C was 510.63±81.58; 534.53±47.62, and 357.14± 83.38g/m2, respectively. Growth rate of A, B, and C was respectively 2.14±0.05, 2.25±0.06, and 2.04±0.10%/day. Feed conversion ratio in treatment A, B, and C were 1.16±0.10, 1.06±0.15, and 1.42±0.11. The survival rate ranged from 71,16-79,63%.  The abundance of heterotrophic bacteria in water with the addition of organic carbon source greater than thanks without carbohydrate addition; B(4,67x106 cfu/ml), A(2,59x106 cfu/ml) and C(2,05x105 cfu/ml). These results showed if the addition of carbohydrates was able to stimulate the growth of heterotrophic bacteria that can be utilized by tilapia as additional nutritious feed.